A jasmonate-responsive bHLH transcription factor TaMYC2 positively regulates triterpenes biosynthesis in Taraxacum antungense Kitag. (January 2023) - Liu, Tingyao; Liao, Jingjing; Shi, Min; Li, Li; Liu, Qun; Cui, Xin; Ning, Wei; Kai, Guoyin
Abstract: Dandelion is a well-known traditional medical herb, also used as functional food. Dandelion possesses many medical properties, such as anti-bacterial and antioxidant activity and contains a variety of triterpenes, such as α-amyrin, β-amyrin, taraxerol and taraxasterol. In this study, we found that triterpenes biosynthesis was promoted by methyl jasmonate (MeJA), while the transcriptional mechanism underlying triterpenes biosynthesis was rarely investigated. Here, a MeJA-induced bHLH transcription factor TaMYC2 was identified. The content of taraxasterol and taraxerol in dandelion was obviously enhanced in overexpression TaMYC2 transgenic lines and expression level of the squalene synthase gene ( TaSS ) was elevated to about 3–5 folds compared with the control lines. Dual-LUC, Y1H and EMSA experiments revealed that TaMYC2 bound to the E-box motif in the promoter of TaSS and activated its transcription. Taken together, this study suggested that TaMYC2 acted as a positive regulator for bioengineering approaches to produce high content triterpenes-producing dandelions. Highlights: MeJA induced the accumulation of total triterpenes (taraxasterol and taraxerol) in Taraxacum antungense Kitag. Most biosynthetic pathway genes involved in taraxasterol and taraxerol biosynthesis were upregulated by MeJA. Overexpression of TaMYC2 promoted taraxasterol and taraxerol accumulation by up-regulating squalene synthase gene expression. TaMYC2 bound to the E-box elements in the promoter of squalene synthase gene and activated its expression.